Perlindungan Hukum Penyewa Rumah Yang Di Jadikan Jaminan Hutang. - Linda Nur Malisa; Neny Noviana Rahma Dhani Putri; Sumriyah Sumriyah (Hakim, 2024)
The application of the principle of good faith in a rental contract can be seen from the extent to which each party carries out its contractual obligations so that the extent to which the parties carry out their obligations is the extent to which their actions are carried out in good faith. One aspect that needs to be understood is that the application of the principle of good faith does not only apply for debtors only, First, how to apply the principle of good faith according to pasal 1338 KUHPerdata, second, what are the general provisions of the principle of good faith Third, what criteria violate the principle of good faith in a rental contract. In a lease, the subject and object of the lease are the existence of the tenant and its whereabouts. The rental contract must be made in writing based on the principle of good faith. Importance. Having a written rental agreement is to remind the parties to respect the agreement that has been agreed upon. An agreement reached verbally will make it difficult to prove an issue.